2018
DOI: 10.1177/1753193418769804
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of modified Lim/Tsai tendon repairs with intra- and extra-tendinous knots

Abstract: We compared the Lim/Tsai tendon repair technique using an extra-tendinous knot with modification using an intra-tendinous knot. The ultimate tensile strength, load to 2 mm gap force, stiffness, mode of failure, location of failure, and time taken to repair each tendon were recorded during a single cycle loading test in 20 tendons with each repair method. We found that the ultimate tensile strength and 2 mm gap force of the modified Lim/Tsai repair with an extra-tendinous knot (56 SD 5 N and 14 SD 2 N, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
1
9
0
3
Order By: Relevance
“…Dear Sir, For a long time, many surgeons have located the knots between two repaired tendon stumps. In the recent report (Chang et al, 2018) about biomechanical comparison of modified Lim/Tsai tendon repairs with intra-and extra-tendinous knots, the authors reported that the strength difference in the ultimate and 2 mm gap forces was actually lower when the knots were placed between two repaired tendons stumps. With placement of suture knots on the tendon surface, the gap resistance force had a small increase of 4 N. The data suggest that the location of knots between tendon stumps may not be beneficial to tendon repairs, but it is hard to see whether knot location will make any major difference in clinical performance of a repair.…”
mentioning
confidence: 99%
“…Dear Sir, For a long time, many surgeons have located the knots between two repaired tendon stumps. In the recent report (Chang et al, 2018) about biomechanical comparison of modified Lim/Tsai tendon repairs with intra-and extra-tendinous knots, the authors reported that the strength difference in the ultimate and 2 mm gap forces was actually lower when the knots were placed between two repaired tendons stumps. With placement of suture knots on the tendon surface, the gap resistance force had a small increase of 4 N. The data suggest that the location of knots between tendon stumps may not be beneficial to tendon repairs, but it is hard to see whether knot location will make any major difference in clinical performance of a repair.…”
mentioning
confidence: 99%
“…Se trata de estudios que analizan desde el punto de vista biomecánico las suturas en el momento cero de la reparación sin tener en cuenta la capacidad de cicatrización del tendón. Los más frecuentemente utilizados cuando se trata de estudios in vitro son los tendones humanos y porcinos, [5][6][7][8] aunque también se han utilizado de perro, 9 oveja, 10 conejo 11 y gallina. 12 Es importante conocer que existen diferencias desde el punto de vista biomecánico.…”
Section: Estudios Biomecánicos De Las Suturas Tendinosas Modelos Utilunclassified
“…33 Hasta hace unos años, la amplia mayoría de cirujanos, utilizaban técnicas de 4 hebras pues resulta un buen equilibrio entre la fuerza máxima y la facilidad de realización de la sutura, 34 sin embargo, la aparición de nuevas configuraciones y suturas tipo loop ha hecho que cada vez más se utilicen configuraciones de 6 u 8 hebras. [5][6][7] • El tipo de agarre al tendón: aunque existen numerosos estudios que defienden que los agarres bloqueados aumentan la resistencia, recientemente Lim y cols han postulado que el aumento de la resistencia de la sutura asimétrica Lim-Tsai respecto a la Lim-Tsai modificada podría deberse a la utilización de puntos de anclaje no bloqueados al tendón, lo que originaría una transmisión más suave de las cargas a través de las hebras. 6 • La tensión de la sutura: se trata de uno de los factores menos estudiados por su dificultad en la aplicación clínica, ya que hasta la fecha no resulta posible cuantificar el acortamiento tendinoso a costa de una determinada tensión a nivel de la sutura del core.…”
Section: Biomecánica De Las Reparaciones Primariasunclassified
See 1 more Smart Citation
“…For each material the standard errors (< n > ≃ 3, extracted from literature) are shown. The materials considered include the 1D nanowires – BaO, LaB 6, Copper tetracyanoquinodimethane (CuTCNQ), Alq3, Si, MgO, AlN, CdS, SiC, W, ITO, CuPC, B, PPy, SnO 2 , InGaN, CNTs, Cu, ZnSe, diamond, GaN, ZnO, ZnMgO, WS 2 , WO, WO 3 , MoO 2 , and ZnS, the 2D platelets – CuO, h‐BN, CbO, MoS 2 , graphene (monolayer, vertically standing, clustered, and few layer), RGO, C nanowall, WS 2 ‐RGO, ZnO and SnS 2 , and the 3D/bulk materials – a ‐diamond, LaB 6 , nanodiamond, DLC, a ‐C, AlN, ta ‐C, Si tips, ZnSe, diamond, Cu tips, ZnO, Ni tips, chemica...…”
mentioning
confidence: 99%